Super Agent : Real Estate Success at the Highest Level - Callaway, Joseph and Callaway, JoAnn, 1944- (Hoboken Wiley, 2014)
Reading Super Agent is like spending a day with two of the most successful real estate agents in America. Joseph and JoAnn Callaway sell 300 to 500 high-end homes per year. Now they share the secrets of their incredible success.
Include Index
Keywords: Real estate agents -- Success in business -- United States